THE PSYCHOLOGICAL ASPECTS OF THE MAIN CHARACTERS OF ROBERT ZEMECKISâ€™ MOVIE â€œFORREST GUMPâ€ - Musyrifah Mahfuddin; Budiarti Putri Uleng (Universitas Andi Djemma, 2023)
The purpose of this study was to learn about the psychological aspects of the main characters in the film